The High mortality and antimicrobial resistance of Klebsiella pneumoniae bacteremia in northern Taiwan - Chyi-Liang Chen; Pin-Chun Hou; Yun-Ting Wang; Hao-Yuan Lee; Ying-Li Zhou; Ting-Shu Wu; Rajendra-Prasad Janapatla; Chien-Chang Yang (Journal of Infection in Developing Countries)
Introduction: Klebsiella pneumoniae, a common hospital- and community-acquired pathogen, is notorious for multidrug resistance. This study aimed to better understand the correlation of clinical presentation and microbiological characteristics of the isolates causing bloodstream infections (BSIs) in Taiwan.